Acupuncture Efficacy on Acute Stroke Patients:A Meta-analysis - Jiaqing LIU; Tongyan LIU; Yun XIANG; Ning ZHAO; Hong ZHANG (康复学报)
Objective:To investigate the effect of acupuncture on acute stroke patients.Methods:Published articles from the earliest date to February,2018 were recalled from the database of Pubmed, Cochrane Library, Embase, CNKI, V1P and Wanfang Data. Study selection, data extraction and quality appraisal were performed by two independent reviewers. The Stata 12.1 software was used for meta-analysis and the GRADE-profile was used to assess the outcome.Results:Eleven trials that represented 1,087 participants were included. The results of meta-analysis indicated that the NIHSS score had no significant meaning between the acupuncture group and the control group [MD=-0.18, (95%CI:-0.41,0.04),P=0.129],the Modified Barthel Index was significantly improved in the acupuncture group [SMD=0.52, (95%CI:0.28,0.76),P<0.01].The GRADE evidence showed that the NIHSS had high quality and the MBI had moderate quality.Conclusion:Acupuncture is effective in improving activities of daily living (ADL) and other functions in stroke patients, but it needs to be verified by more large-scale and high-quality randomized studies.